Implementasi Otokoreksi Ejaan Bahasa Indonesia pada Kamus Istilah Elektronika - Wibowo, Hilal Aji; Wibawanto, Hari (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
A dictionary now is available online or offline , text search resulted in the process of search is long because the database on the server is online .While application offline there are still several application a little use the feature search without text correction and auto correction text.With this software